Late-spring Turfgrass Establishment without Herbicides - Andrew R. Muntz; T. Karl Danneberger; John R. Street; David S. Gardner (HortTechnology, 2023)
Spring establishment of turfgrass that is managed without herbicides is subject to weed competition, resulting in reduced turfgrass cover. The objective of this experiment was to find an acceptable method for spring turfgrass establishment without the use of pesticides. Thirty-six treatments consisting of three soil amendments combined with three turfgrass species or mixes, and four topdressings or fertilizers in a randomized complete block design were tested. Nutrient-deficient fill soil, fill soil blended with topsoil, and fill soil blended with leaf compost were used as growing media. ‘Firenza’ tall fescue (Schedonorus arundinaceus), an 80/20 mix of ‘Nu Destiny’ kentucky bluegrass (Poa pratensis) and ‘Nexus XD’ perennial ryegrass (Lolium perenne), respectively, and ‘Firefly’ hard fescue (Festuca trachyphylla) were grown with topdressings consisting of biosolids, ash-amended biosolids, 16N–12.2P–3.3K starter fertilizer, and an unfertilized control. The treatments were mowed at 3 inches about once per week. Irrigation was supplied by an overhead sprinkler system (1 inch/week). During the 2010 field study, treatments of tall fescue established in a leaf compost–amended root zone were significantly denser and had a greater percentage of cover (P ≤ 0.05) compared with all other treatments. In 2011, treatments of tall fescue established in fill soil– and leaf compost–amended soils were significantly denser and had a greater percentage of cover (P ≤ 0.05) compared with all other treatments. Kentucky bluegrass/perennial ryegrass and hard fescue treatments had significantly lower (P ≤ 0.05) levels of establishment compared with tall fescue. Topdressing treatments resulted in no significant difference (P ≤ 0.05) in turfgrass establishment.